Homework—Hopework - Pasha Tretyakova (The February Journal, 2025)
What is possible when a home is not home because home is love and love contains hope? Do you not have hope? Does your place of origin hang around your neck like a problem? In the wake of the war that Russia has been perpetrating in Ukraine, with the full-scale invasion beginning on 24 February 2022, the author negotiates in this autoethnographic essay with performative elements what it means to see, love, lose, and have hope in your home.